2019
DOI: 10.1186/s12871-019-0750-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined ultrasound and nerve stimulator-guided deep nerve block may decrease the rate of local anesthetics systemic toxicity: a randomized clinical trial

Abstract: Background Ultrasound guidance might decrease the incidence of local anesthetics systemic toxicity (LAST) for many peripheral nerve blocks compared with nerve stimulator guidance. However, it remains uncertain whether ultrasound guidance is superior to nerve stimulator guidance for deep nerve block of the lower extremity. This study was designed to investigate whether deep nerve block with ultrasound guidance would decrease the incidence of LAST compared with that with nerve stimulator guidance, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…e results showed that the VAS scores and PONV scores of patients with TAP block decreased evidently at 3 h, 6 h, and 12 h after surgery, and the number of patients who used tramadol for analgesic remedy after surgery was reduced, which greatly improved patient satisfaction. e results were consistent with those of Zhang et al [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…e results showed that the VAS scores and PONV scores of patients with TAP block decreased evidently at 3 h, 6 h, and 12 h after surgery, and the number of patients who used tramadol for analgesic remedy after surgery was reduced, which greatly improved patient satisfaction. e results were consistent with those of Zhang et al [14].…”
Section: Discussionsupporting
confidence: 93%
“…erefore, TAP block requires the adoption of appropriate drug concentration and dosage [14]. In this work, 20 mL of 0.375% ropivacaine was used to observe the block plane distribution between the two groups within 30 minutes after the TAP block, and the difference was not considerable (P < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Combining ultrasound guidance and nerve stimulation may be helpful to safely confirm lumbar plexus sonoanatomy, and to place the tip of the needle just close to the targeted nerve. The dual guidance aims to decrease the incidence LAST and/or nerve injury, particularly while performing a deep nerve block such as a PLPB 11 . A nerve stimulator malfunction or an electrical disconnection may occur during the nerve block procedure 12,13 .…”
Section: Discussion Of the Technical Report And Algorithmmentioning
confidence: 99%
“…Therefore, epidemiological factors such as gender and age have gradually drawn attention in a large number of clinical studies, and gender is one of the important in uencing factors in the diagnostic models and prognostic analysis models of some diseases. For example, in a study of combined ultrasound and nerve stimulator-guided deep nerve block, the research objects were also grouped by sex (40). Similarly, in a study of risk factors for osteoporosis and associated fractures, females have long been listed as a risk factor, and due to the secretion of female oestrogen, it has also become a point of consideration in the treatment of osteoporosis patients (41).…”
Section: Research Focused On Ultrasound In Orthopaedicsmentioning
confidence: 99%